Creativity in distinctive brand assets - Velykytė, Gabija (Creativity Studies, 2023)
The article discloses creativity in developing brand assets and explores the relationship between creativity, distinctive brand assets, and divergent thinking. The scientific novelty of an article that explores the combination of distinctive brand assets and divergent thinking might lie in its potential to shed new light on how branding strategies can be used to foster creativity. By examining how certain visual and auditory cues associated with a brand can activate divergent thinking, the study could provide insights into how marketers can design more effective branding campaigns that not only increase brand recognition but also inspire consumers to think outside the box. Distinctive brand assets are unique visual and auditory cues that help consumers identify and differentiate a brand from its competitors. Divergent thinking is generating multiple ideas and solutions to a problem. The article argues that successful distinctive brand assets could result from divergent thinking and creativity, as they enable brands to create assets that are not only distinctive but also emotionally resonant and memorable. Ultimately, the article demonstrates how divergent thinking and creativity are critical components in the development and success of distinctive brand assets, which are an essential part of a brand’s overall marketing strategy.